Uma questão de opinião: Zé Kéti, Samba e transformações urbanas na Cidade do Rio de Janeiro (1950-1979) - Barbeiro, Adriana Santoleri Villa (2014)
This study is part of the Cultural History perspective, particularly, the approach related to the urbanization process of Brazilian cities and the identities construction linked to its crioulo approach. The main aim of this research is to study how the slums intensification process in Rio de Janeiro city came about, between the decades of 1950 and 1980, and also the answers and reflexions of this action characterized in building identities and the carioca musical production of that period, analyzed per the work of the Samba composer, José Flores de Jesus, the Zé Kéti. We seek to understand, through compositions and also biography of Zé Kéti, what Édouard Glissant called "arrué", the mix of irruption and impulse, reality and unreality, characteristics, which we believe been present, not only in the productions that are analyzed in this writing, but also, in Samba itself (as well as in other musical genres created in the "Atlântico Negro" border), and even, in the carioca slum identity and the Brazilian "people" that we will try to elucidate. Thus, we will try to observe how the economic and politic transformations, carried out in studied period, were reflected not only in the transformation of public space disordered, but also, in the way we think and feel the situations that were assumed increasingly more present in the lives of many of the less favored population So, starting from a particular reality, it is desired to represent another contribution among the recent, and increasingly relevant, work about the processes of identities construction around the "Atlântico Negro" and the transformations of Brazilian cities , beyond enable a less pragmatic and deforming look with which realize this same situation along an entire History